1998
DOI: 10.1021/bi981939o
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Extracellular Ligand-Binding Domain of the Type II Activin Receptor

Abstract: The binding of a ligand to cell surface receptors initiates a cascade of intracellular signals that generate responses to the external stimuli. Thus, this event plays a pivotal role in the mechanism of transmembrane signaling. Activin is a member of a cytokine family that is involved in diverse biological processes. To study the structural basis that underlies the transmembrane signaling mechanism, we have overexpressed the soluble extracellular domain of the type II activin receptor from mouse (ActRII-ECD). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 35 publications
2
91
0
1
Order By: Relevance
“…Importantly, in these two exons, amino acid substitutions represent the most common type of mutation, indicating conserved structural and functional requirements of this region for BMPR-II signaling activity. In vitro mutagenesis and X-ray crystallography studies identified 10 cysteine residues conserved across the related type II BMP, MIS, and activin receptors, each of which is necessary for receptor ligand protein folding of the ligand domain [Greenwald et al, 1999]. FPAH-causing missense mutations have now been identified for eight of the 10 cysteine residues, and of those studied by transient transfection of GFP-or myc-tagged BMPR2 constructs, each appears to lead to significant protein misfolding and/or cytoplasmic retention [Nishihara et Frequency refers to the number of times recurrent mutation has been identi¢ed by each investigation.…”
Section: Pattern and Distribution Of Mutations Across The Functional mentioning
confidence: 99%
“…Importantly, in these two exons, amino acid substitutions represent the most common type of mutation, indicating conserved structural and functional requirements of this region for BMPR-II signaling activity. In vitro mutagenesis and X-ray crystallography studies identified 10 cysteine residues conserved across the related type II BMP, MIS, and activin receptors, each of which is necessary for receptor ligand protein folding of the ligand domain [Greenwald et al, 1999]. FPAH-causing missense mutations have now been identified for eight of the 10 cysteine residues, and of those studied by transient transfection of GFP-or myc-tagged BMPR2 constructs, each appears to lead to significant protein misfolding and/or cytoplasmic retention [Nishihara et Frequency refers to the number of times recurrent mutation has been identi¢ed by each investigation.…”
Section: Pattern and Distribution Of Mutations Across The Functional mentioning
confidence: 99%
“…Yet another possibility is that differences exist between the affinity of Acvr2b-1 and -2 to MSTN1 and MSTN2. Interestingly, a 1000-fold excess of mouse ACVR2B-ECD to activin was needed in order to achieve about 50% inhibition of activin-induced FSH secretion from pituitary cells (Greenwald et al 1998). This later study showed binding between the two by cross-linking experiments, using radiolabeled activin and mouse ACVR2-ECD expressed in P. pastoris.…”
Section: Inhibition Of Mstn Activity By Saacvr2b-1-ecdmentioning
confidence: 92%
“…Alignment of deduced amino acid sequences was performed by using DNAMAN software (Lynnon Biosoft, Canada). In order to understand the secondary structures of the extracellular domain and kinase domain of grass carp ActRIIA, secondary structure-based alignment was conducted with the known structures of mouse ActRII and human ActRIIB (Greenwald et al, 1999;Han et al, 2007). Furthermore, modeling of tertiary structure for grass carp ActRIIA was achieved by using the automated compara-tive protein modeling server SWISS-MODEL (http:// swissmodel.expasy.org) with the first approach mode.…”
Section: Isolation Of the Full-length Cdna Of Actriiamentioning
confidence: 99%
“…Furthermore, modeling of tertiary structure for grass carp ActRIIA was achieved by using the automated compara-tive protein modeling server SWISS-MODEL (http:// swissmodel.expasy.org) with the first approach mode. In this case, the crystal structures of the extracellular ligand-binding domain of mouse ActRII (PDB 1bteB) (Greenwald et al, 1999) and human ActRIIB kinase domain (PDB 2qluA) (Han et al, 2007) were utilized as the templates to create the ligand-binding domain and the intracellular kinase domain of grass carp ActRIIA, respectively. The three-dimensional (3D) models were visualized with Molsoft ICM software (Molsoft L.L.C., USA).…”
Section: Isolation Of the Full-length Cdna Of Actriiamentioning
confidence: 99%
See 1 more Smart Citation